(untitled) (Al-Academy, 2025)
Traditional architecture in the Najd region is one of the most prominent manifestations of cultural identity in the Kingdom of Saudi Arabia. Its material and decorative components bear vivid evidence of the aesthetic and social values that have characterized Najdi society throughout history. This research aims to analyze the symbolic connotations of Najdi architectural decorations in Al Tuwaijri House in Al Majma’ah Governorate. The study used a descriptive and analytical approach to uncover and analyze these connotations. To achieve results related to the research objectives, a sample of eight decorations, distributed among geometric, botanical, and symbolic motifs, was studied. The results demonstrated that the Al-Tuwaijri House is distinguished by its unique decorative richness, combining a variety of elements with meticulous execution, making it one of the most important examples which embody the artistic character of Najdi architecture in Al-Majma’ah. The research revealed the integration of the house’s decorative elements, as the decorations were not executed in isolation from the building itself, but rather harmonized with the architectural rhythm of the entrances, portico, and majlis. This reflects the craftsman’s awareness of the relationship between decoration and the architectural space and the financial capabilities and status of the Al-Tuwaijri family. The Gypsum decorations embody a symbolic and cultural dimension, reflecting the system of social values in Najd, such as generosity, solidarity, and religiosity. Based on the results of the study, the current study reached a set of recommendations, the most important of which are: digital documentation of the Gypsum decorations and their restoration using traditional materials, while employing the traditional decorative vocabulary in contemporary designs that contribute to preserving authenticity and reviving local identity.